Controlled Nanopore Sizes in Supraparticle Supports for Enhanced Propane Dehydrogenation with GaPt SCALMS Catalysts - Madubuko, Nnamdi; Sultan, Umair; Carl, Simon; Lehmann, Daniel; Zhou, Xin; Soegaard, Alexander; Taccardi, Nicola; Apeleo Zubiri, Benjamin; Wintzheimer, Susanne; Spiecker, Erdmann; Haumann, Marco; Vogel, Nicolas; et al. (ACS Applied Nano Materials, 2024)
The efficient immobilization of GaPt liquid metal alloy droplets onto tailored supports improves catalytic performance by preventing coalescence and subsequent loss of active surface area. Herein, we use tailored supraparticle (SP) supports with controlled nanopores to systematically study the influence of pore sizes on the catalytic stability of GaPt supported catalytically active liquid metal solution (SCALMS) in propane dehydrogenation (PDH). Initially, GaPt droplets were prepared via an atom-efficient and scalable ultrasonication method with recycling loops to yield droplets <300 nm. Subsequently, these droplets were immobilized onto SiO2-based SPs with controlled pore sizes ranging from 45 to 320 nm. Catalytic evaluations in PDH revealed that GaPt immobilized on SPs with larger pores demonstrated superior stability over 15 h time-on-stream evidenced by reduced deactivation rates from 0.046 to 0.026 h-1. Nanocomputed tomography and identical location SEM confirmed the successful immobilization of GaPt droplets within the interstitial sites formed by the primary particles constituting the SPs. These remained unchanged before and after the catalytic reaction, demonstrating efficient coalescence prevention. Our findings underscore the importance of support pore size engineering for improving the stability of GaPt SCALMS catalysts and highlight, particularly, the high potential of using SPs in this context.
CRIS-Team Scopus Importer:2024-11-22
Keywords: catalysis; gallium; liquid metal; porous supports; propane dehydrogenation; SCALMS; supraparticles

Structural Evolution of GaOx-Shell and Intermetallic Phases in Ga-Pt Supported Catalytically Active Liquid Metal Solutions - Carl, Simon; Will, Johannes; Madubuko, Nnamdi; Götz, Alexander; Przybilla, Thomas; Wu, Mingjian; Raman, Narayanan; Wirth, Janis; Taccardi, Nicola; Apeleo Zubiri, Benjamin; Haumann, Marco; Wasserscheid, Peter; et al. (Journal of Physical Chemistry Letters, 2024)
We present a comprehensive scale-bridging characterization approach for supported catalytically active liquid metal solutions (SCALMS) which combines lab-based X-ray microscopy, nano X-ray computed tomography (nano-CT), and correlative analytical transmission electron microscopy. SCALMS catalysts consist of low-melting alloy particles and have demonstrated high catalytic activity, selectivity, and long-term stability in propane dehydrogenation (PDH). We established an identical-location nano-CT workflow which allows us to reveal site-specific changes of Ga-Pt SCALMS before and after PDH. These observations are complemented by analytical transmission electron microscopy investigations providing information on the structure, chemical composition, and phase distribution of individual SCALMS particles. Key findings of this combined microscopic approach include (i) structural evolution of the SCALMS particles’ GaOx shell, (ii) Pt segregation toward the oxide shell leading to the formation of Ga-Pt intermetallic phases, and (iii) cracking of the oxide shell accompanied by the release of liquid Ga-Pt toward the porous support.
CRIS-Team Scopus Importer:2024-05-10

Supraparticles on beads for supported catalytically active liquid metal solutions - the SCALMS suprabead concept - Zimmermann, Thomas; Madubuko, Nnamdi; Groppe, Philipp; Raczka, Theodor; Dünninger, Nils; Taccardi, Nicola; Carl, Simon; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Wasserscheid, Peter; Mandel, Karl; Haumann, Marco; et al. (Materials Horizons, 2023)
A novel GaPt-based supported catalytically active liquid metal solution (SCALMS) material is developed by exploiting the suprabead concept: Supraparticles, i.e. micrometer-sized particles composed of nanoparticles assembled by spray-drying, are bonded to millimeter-sized beads. The suprabeads combine macroscale size with catalytic properties of nanoscale GaPt particles entrapped in their silica framework.
Created from Fastlane, Scopus look-up

Top-down vs. bottom-up synthesis of Ga–based supported catalytically active liquid metal solutions (SCALMS) for the dehydrogenation of isobutane - Raman, Narayanan; Söllner, Jakob; Madubuko, Nnamdi; Nair, Sharanya Sukumar; Taccardi, Nicola; Thommes, Matthias; Haumann, Marco; Wasserscheid, Peter (Chemical Engineering Journal, 2023)
Supported catalytically active liquid metal solutions (SCALMS) catalysts consist of a liquid metal solution of an active metal (e.g., Pd, Rh, Pt, Ni) in a low melting metal (e.g., Ga, In, Sn) deposited on a porous support material. In the current study, we extend and optimize the recently developed top-down synthesis protocol (ultrasonication of gallium metal) to prepare GaPd, GaRh and GaPt SCALMS systems. We compare the morphological differences in the obtained catalyst materials achieved between this approach and the more traditional bottom-up synthesis protocol (in situ thermal decomposition of triethylamino-gallane complex) using electron microscopy. Moreover, the spatial distribution of the catalytically active material in the porous alumina support is evaluated using high resolution argon physisorption measurements. Both techniques strongly indicate that the bottom-up approach leads to a high degree of pore penetration while the gallium droplets are largely on the outer surface in case of the top-down method. Changes to the surface chemistry of the support were also investigated by means of NH3/CO2 temperature programmed desorption. All catalytic systems synthesized by the two synthesis methods, i.e., GaPd, GaRh and GaPt, were tested in a quartz, fixed-bed tubular reactor for isobutane dehydrogenation. All SCALMS materials, irrespective of their individual synthesis protocol, were significantly more active than their pure metal counterparts. The SCALMS catalyst prepared using the bottom-up approach showed initial productivity of 407 gbutenes molM–1 min−1, 832 gbutenes molM–1 min−1, and 963 gbutenes molM–1 min−1 for the GaPd, GaRh and GaPt respectively. These values represent more than twice the initial activity obtained with the top-down synthesized counterparts. This activity difference can be explained by the analytically determined difference in liquid metal droplet size distribution.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Coking; Dehydrogenation; Gallium; Liquid metal; SCALMS; Supported catalyst